Oxidation and thermal stability enhancement of emulsified palm oil methyl ester in diesel engine / Syeda Reham Shahed - Syeda, Reham Shahed (2017)
Energy coming from fossil fuels are non-renewable, therefore, they have a negative effect on the environment namely- greenhouse effect or global warming. Researchers are conducting a lot of studies on renewable fuel to practice it as an alternative fuel for transportation and other uses. Biofuel has been widely accepted as a very potential renewable energy that can replace the conventional use of fossil fuel for diesel engine. Biodiesels can be used in conventional diesel engine without any modification and can also reduce harmful emissions. However, biodiesel have low oxidation stability which sometimes affect badly while storing and using it as fuel. This research is aimed to improve oxidation stability as well as thermal stability of biodiesel through emulsification process. In the emulsification process water is added to biodiesel with the help of surfactant (TritonX-100) and co-surfactant (ethanol) to make the mixture stable. FTIR (Fourier transform infrared spectroscopy) and proton NMR (Nuclear magnetic resonance) are used to analyze the chemical bond characteristics of biodiesel emulsion. Oxidation stability, thermal stability and lubrication characteristics of emulsified palm oil biodiesel is then investigated. It has been found that the oxidation stability of emulsified biodiesel is 102% higher than diesel and 27% higher than neat biodiesel. Thermo-gravimetric analysis shows improved thermal property of biodiesel emulsion compared to both diesel and neat biodiesel. The friction and wear test of emulsified biodiesel conducted with four ball tribo tester according to ASTM 4172 method (1200 rpm, 75°C temperature and 40 kg load). The improved lubricating performance found with emulsified biodiesel due to lower coefficient of friction and wear scar diameter compared to petroleum diesel fuel and neat biodiesel. In conclusion, addition of TritonX-100 and ethanol with small amount of water with biodiesel improves its oxidation and thermal stability and own improved lubricating characteristics compared to diesel and biodiesel fuel.